SAT0133 Golimumab 3-year safety update: An analysis of pooled data from the long term extensions of randomized, double-blind, placebo-controlled studies in rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis. (23rd January 2014) - Kay, J.; Fleischmann, R.; Keystone, E.; Hsia, E.C.; Doyle, M.K.; Hsu, B.; Mack, M.; Beutler, A.; Braun, J.; Kavanaugh, A.
Abstract : Objectives: To present analysis of pooled data through approx 3yrs of follow-up from 5 ongoing golimumab (GLM) Ph3 SC trials across rheumatological indications and through 1yr in a completed Ph2 RA trial. Methods: SC placebo (PBO) or GLM (50mg or100mg) was administered q4wks in Ph3 and q2/4wks in Ph2 trials. After wk24/52, pts in the Ph3 studies entered LTE and received GLM50mg or 100mg q4wks in an unblinded fashion. Dose escalation from 50mg to 100mg was allowed; no dose reduction permitted. Concomitant meds included DMARDs (mostlyMTX). AE were analyzed based on treatment received prior to occurrence of AE. Because pts could cross-over from PBO to GLM or increase GLM dose from 50mg to 100mg in cases of inadequate response in the Ph3 trials, a pt may appear in more than one column. Due to the short duration of the PBO-controlled portion, comparisons between (btwn) the GLM and PBO grps are limited. Results: In combined Ph2/3 trials, 674pts received PBO, 1317 GLM50mg, and 1571 GLM100mg through 3yrs. In Ph3, 4.9%, 7.4%, and 10.5% of PBO, GLM50, GLM100mg pts, respectively, DC'd due to AE through 3yrs. In Ph2, 5.9% of PBO and 8.0% of GLM pts DC'd due to AE through 1yr. The incidences per 100PY of deaths, serious infections (including TB, opportunistic infections [OI]), demyelination, and malignancies are presented. Injection site reactions were low; most were mild, and 2 cases led to DC. No GLM SC-treated pt developed anaphylaxis/serum sickness-like reaction. Malignancies occurring during the 5 Ph3 and 1 Ph2 included skin cancers, solid tumors, and lymphoma. In comparison to SEER, overall incidence of malignancies in GLM-and PBO-treated pts was similar to that expected in the general US population. Incidence of lymphomas per 100 pt-years of follow-up was greater in the GLM100mg dose grp through 3yrs and higher than that expected in the general US population. Conclusions: The safety of continued SC GLM exposure, demonstrates that GLM was generally well-tolerated with overall low rates of DC due to AEs. Safety profiles were generally similar btwn GLM dose with exception of higher rates of serious infections, including TB and OI, and lymphoma in the GLM100mg grp. Results are confounded by LTE design in which pts could receive GLM100mg after being exposed to GLM50mg with higher GLM dose used for pts with more active disease, and by limited exposure to PBO making the comparisons btwn PBO and treatment grps of less value. Disclosure of Interest: J. Kay Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, R. Fleischmann Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, E. Keystone Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, E. Hsia Employee of: Janssen Research & Development, LLC, M. Doyle Employee of: Janssen Research & Development, LLC, B. Hsu Employee of: Janssen Research & Development, LLC, M. Mack Employee of: Janssen Research & Development, LLC, A. Beutler Employee of: Janssen Research & Development, LLC, J. Braun Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, A. Kavanaugh Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study